2023
DOI: 10.48550/arxiv.2302.14070
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Search for Thermonuclear Transients from the Tidal Disruption of a White Dwarf by an Intermediate Mass Black Hole

Abstract: The close encounter of a white dwarf (WD) with a black hole (BH) could result in the tidal disruption of the WD. During this encounter, the WD can undergo a thermonuclear explosion due to its tidal compression, resulting in an optical transient similar to a Type Ia supernova (SN Ia), hereafter a Ia-TDE. Nevertheless, this will only be physically observable if the BH is 10 5 M . Finding a Ia-TDE would therefore imply the discovery of an intermediate mass black hole (IMBH) 10 5 M . Here, we search the entire Zwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 107 publications
0
1
0
Order By: Relevance
“…Since their X-ray emission has been modeled directly as the result of accretion (i.e., no jet requirement), our estimated disruption rates of 0.1 Myr −1 would give plausibility to this interpretation for at least a fraction of transients. Most recently, Gomez & Gezari (2023) has shown that SN 2020lrt may be a candidate for a WD being tidally compressed and disrupted by an IMBH.…”
Section: Prompt Tidal Disruption (Near Parabolic Orbit)mentioning
confidence: 99%
“…Since their X-ray emission has been modeled directly as the result of accretion (i.e., no jet requirement), our estimated disruption rates of 0.1 Myr −1 would give plausibility to this interpretation for at least a fraction of transients. Most recently, Gomez & Gezari (2023) has shown that SN 2020lrt may be a candidate for a WD being tidally compressed and disrupted by an IMBH.…”
Section: Prompt Tidal Disruption (Near Parabolic Orbit)mentioning
confidence: 99%